2009
DOI: 10.1159/000200980
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavones – Mechanism of Action and Impact on Breast Cancer Risk

Abstract: Isoflavones are plant-derived substances with weak estrogenic effects. Asian populations are high consumers of soy products which are rich in isoflavones. The lower breast cancer incidence in Asian women compared with Western women has been associated with the possibility of a preventive isoflavone effect on cancer risk. The aim of this review is to give an overview of current research data on the influence of isoflavones on the risk of primary breast cancer development as well as the risk of recurrence in bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…Pathway analysis of the high-genistein signature revealed overrepresentation of pathways that regulate cell growth and proliferation in tumors of the high-genistein group (P < .001). DAVID analysis of overexpressed genes in the high-genistein group revealed that 18 of 23 categories represented cell cycle functions (Bonferroni P < .001, FDR < 0.01) (Supplementary Table 6, available online) (33). Similarly, IPA revealed that the Top Biological Functions and Network Modules of the 126 DE genes were cellular growth and proliferation, cell cycle, cell death and survival, cell development, and nucleic acid metabolism (P < .001) (Supplementary Figure 2, A and B, and Supplementary Table 7, available online).…”
Section: Genome-wide Expression Analysis In Posttreatment Specimensmentioning
confidence: 99%
“…Pathway analysis of the high-genistein signature revealed overrepresentation of pathways that regulate cell growth and proliferation in tumors of the high-genistein group (P < .001). DAVID analysis of overexpressed genes in the high-genistein group revealed that 18 of 23 categories represented cell cycle functions (Bonferroni P < .001, FDR < 0.01) (Supplementary Table 6, available online) (33). Similarly, IPA revealed that the Top Biological Functions and Network Modules of the 126 DE genes were cellular growth and proliferation, cell cycle, cell death and survival, cell development, and nucleic acid metabolism (P < .001) (Supplementary Figure 2, A and B, and Supplementary Table 7, available online).…”
Section: Genome-wide Expression Analysis In Posttreatment Specimensmentioning
confidence: 99%
“…Yet, there are data to support drinking green tea in order to reduce the risk of recurrence [44][45][46]. Whilst isoflavones have the potential to reduce the breast cancer incidence, particularly when consumed on a regular basis beginning before puberty [47], their consumption as secondary prevention after breast cancer appears critical: Particularly in the estrogen-deprived environment under aromatase inhibitors, isoflavones (e.g. genistein from soy) could stimulate hormone receptor-positive cells to divide.…”
Section: Other Supplementsmentioning
confidence: 99%
“…Therefore, estrogen-induced cell proliferation has been a major focus in breast cancer research. Despite the substantially lower breast-cancer prevalence in populations with a high soy consumption (1,2), the findings of Allred et al (3)(4)(5)(6)(7) provoked a heated debate about the safety of dietary phytoestrogens, such as isoflavones, especially for patients with existing estrogen-sensitive tumors and women at a high risk of developing breast cancer (1,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%